High-fidelity copies from a symmetric 1→2 quantum cloning machine - Siomau, Michael; Fritzsche, Stephan (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2010)
A symmetric 1→2 quantum cloning machine(QCM) is presented that provides high-fidelity copies with0.90≤ F≤0.95 for all pure (single-qubit) input statesfrom a given meridian of the Bloch sphere. Emphasize is placedespecially on the states of the (so-called) Eastern meridian, thatincludes the computational basis states |0〉,|1〉together with the diagonal state $|{+}\rangle \,=\, \frac{1}{\sqrt{2}}(|{0}\rangle \,+\, |{1}\rangle)$, for which suggested cloningtransformation is shown to be optimal. In addition, we also showhow this QCM can be utilized for eavesdropping in Bennett’s B92protocol for quantum key distribution with a substantial highersuccess rate than obtained for universal or equatorial quantumcopying.